Ποίησις, Hervorbringen, ἀλήθεια: Spunti per una ontologia dell'arte (Materiali di Estetica. Terza serie, 2020)
This paper points out the ontological bond art shares with truth by providing a different perspective on the question of production. Following a brief genealogical survey of the greek word ποίησις, it will be highlighted how the meaning of this notion can resonate with some suggestions emerging from Martin Heidegger's studies on the concept of ἀλήθεια and with the very german translation he gives of the aforementioned ποίησις. This is the necessary condition under which the analysis of a more specific typology of production, namely that of a piece of art, may then be carried out.
Keywords: Classical philosophy; Martin Heidegger; Ontology of art